Orientasi Smart Parenting dalam Membangun Tumbuh Kembang Peserta Didik - Wa Ode Citra Verawati; Nur Fazila; Diana Safila; Sherly Sherly; Muhammad Yusnan; Sandra Elfira Alhasan (Medan Resource Center, 2023)
This study aims to examine the effect of Smart Parenting on the Formation of Children's Character. Parents can use technology and modern approaches to educate children. however, there needs to be more supervision of child caregivers, which affect the child's development. This study used a quantitative method by conducting a regression test. Data is collected through the distribution of questionnaires. The results of the study show that Smart Parenting has a positive influence on the formation of children's character. This is because Smart Parenting provides opportunities for children to participate in decision-making, respect children's opinions and feelings, provide support and guidance according to children's needs and interests, and use technology wisely and responsibly. The conclusion of this study is that Smart Parenting is an effective and relevant parenting style with the times to shape better children's character.